Green and Sustainable Cyber-Physical Security Solutions for Body Area Networks - Venkatasubramanian, K.K.; Banerjee, A.; Gupta, S.K.S. (2009 Sixth International Workshop on Wearable and Implantable Body Sensor Networks, 2009)
Wireless sensor-based Body Area Networks (BAN) can play a major role in providing individualized health-care. Given their limited power sources, sensors in BAN have to be energy-efficient to ensure longevity and safety of the network. Recent years have seen the emergence of a new class of security solutions for BANs, called cyber-physical security solutions, which enable plug-n-play secure communication within a BAN using environment derived features. However, due to this environment-coupled nature, they require signal processing and mathematical routines which can be potentially very energy-intensive for individual sensors. In this paper, we characterize the "energy footprint" of a cyber-physical security solution, the Physiological signal based Key Agreement (PKA). The goal is to - 1) compute PKA's energy consumption, and 2) determine whether prominent energy scavenging techniques can be used to meet its requirements. Our results show that the energy requirements of PKA is small and is sustainable by many of the prominent energy scavenging techniques, such as body heat and ambulation, making it a "green" solution for large scale deployments.